FIKK Education Student Knowledge Survey on Sports Nutrition - Muhammad Fadlih, Andi; Ihsan, Andi; Yani, Ahmad (SHOOTING: Journal of Sport, Health, and Education, 2024)
Sports nutrition has a direct impact on the current physical condition of the body or the physical preparation of the athlete depending on the nutritional status of the athlete involved. The sample consisted of 18 postgraduate students specializing in Physical Culture, Faculty of Sports and Physical Education from Makassar State University. When we look at the overall results, it can be concluded that the students' knowledge of sports nutrition is at a very satisfactory level, especially when comparing the results with the previous research knowledge of athletes and coaches about sports nutrition. Out of a total of 360 responses, 310 answers were correct, or 86.1%. No matter how talented an athlete is in the sport they train or train, motivated and well-trained, the line between defeat and victory is usually very thin, and as the most important link imposes sports nutrition. The results of an athlete and that you can depend on the quality, quantity and timing of the diet entry.